2007
DOI: 10.1128/jcm.00077-07
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage Galactomannan in Diagnosis of Invasive Pulmonary Aspergillosis among Solid-Organ Transplant Recipients

Abstract: We review the experience at our institution with galactomannan (GM) testing of bronchoalveolar lavage (BAL) fluid in the diagnosis of invasive pulmonary aspergillosis (IPA) among solid-organ transplant recipients. Among 81 patients for whom BAL GM testing was ordered (heart, 24; kidney, 22; liver, 19; lung, 16), there were five cases of proven or probable IPA. All five patients had BAL GM of >2.1 and survived following antifungal therapy. The sensitivity, specificity, and positive and negative predictive value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(141 citation statements)
references
References 28 publications
8
123
2
2
Order By: Relevance
“…5 Another study showed that among 81 patients with solid-organ transplant, the sensitivity and specificity of detecting galactomannan in bronchoalveolar lavage was 100% and 90% in diagnosing invasive aspergillosis (cutoff > 1). 8 False-positive cases are reported frequently, especially in patients with lung transplant, owing to a high rate of aspergillus colonization in these patients. 8 Another study of 116 lung transplant cases reported 60% sensitivity and 95% specificity for bronchoalveolar lavage galactomannan measuring (cutoff > 0.5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Another study showed that among 81 patients with solid-organ transplant, the sensitivity and specificity of detecting galactomannan in bronchoalveolar lavage was 100% and 90% in diagnosing invasive aspergillosis (cutoff > 1). 8 False-positive cases are reported frequently, especially in patients with lung transplant, owing to a high rate of aspergillus colonization in these patients. 8 Another study of 116 lung transplant cases reported 60% sensitivity and 95% specificity for bronchoalveolar lavage galactomannan measuring (cutoff > 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…8 False-positive cases are reported frequently, especially in patients with lung transplant, owing to a high rate of aspergillus colonization in these patients. 8 Another study of 116 lung transplant cases reported 60% sensitivity and 95% specificity for bronchoalveolar lavage galactomannan measuring (cutoff > 0.5). 7 In comparison, our study had a higher sensitivity and specificity with both methods (serum and bronchoalveolar lavage galactomannan measuring) in diagnosing invasive aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…72 In contrast to the serum assay, BAL GM seems to perform well in SOT recipients. 73,74 There are no data to support the use of BDG testing in BAL. 69 Multiple causes of false-positive results for both BDG and GM have been reported, such as concomitant bacterial infections, b-lactam antibiotics, blood transfusions, blood-derived products, gluconate sodium-containing products, renal replacement therapy, and cross-reactivity with other fungi.…”
Section: Improving Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%